Predictors and timing of recovery in patients with immediate facial nerve dysfunction after parotidectomy - Tung, Bau-Kuei; Chu, Pen-Yuan; Tai, Shyh-Kuan; Wang, Yi-Fen; Tsai, Tung-Lung; Lee, Tsung-Lun; Hsu, Yen-Bin (Head & neck, 2014)
Background Identification of predictors for permanent facial nerve dysfunction and timing of recovery are important for the management of patients who experience immediate facial nerve dysfunction after parotidectomy. Methods In this 6‐year retrospective cohort study, 54 such patients were analyzed to determine the associated prognostic factors and timing of recovery. Results All 54 patients with immediate postparotidectomy facial nerve dysfunction experienced weakness of the marginal mandibular branch; 7% had coexisting zygomatic branch dysfunction. Forty‐five patients (83%) achieved complete recovery. The cumulative rates of recovery at 1 month, 3 months, 6 months, and 1 year postparotidectomy were 31%, 70%, 81%, and 83%, respectively. Immediate postparotidectomy facial nerve dysfunction higher than House–Brackmann (H–B) grade III was the only poor prognostic factor (odds ratio, 6.6; 95% confidence interval, 1.2–35.4). Advanced age, malignant tumor, larger tumor size, and postoperative steroids did not exert significant effect on the recovery of facial nerve dysfunction. Conclusion Immediate postparotidectomy facial nerve dysfunction greater than H–B grade III was a significant predictor of permanent dysfunction. Only 2% of patients achieved any improvement beyond 6 months postoperatively. © 2013 Wiley Periodicals, Inc. Head Neck 36: 247–251, 2014